2015
DOI: 10.1515/zireb-2015-0002
|View full text |Cite
|
Sign up to set email alerts
|

The Relevance of Trend Variables for the Prediction of Corporate Crises and Insolvencies

Abstract: Abstract:This study investigated the potential of a specifi c trend, defi ned as the relative change of accounting ratios for two consecutive years, to improve the classifi cation accuracy and model performance of insolvency prediction models based on multivariate linear discriminant analysis. The results show that the respective trend can include information from both consecutive years, but this informational content could not be exploited to improve early detection of corporate crises and insolvencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 111 publications
0
3
1
Order By: Relevance
“…The result shows that the profitability of the firms in manufacturing industry of Bangladesh is positively influenced by the Liquidity of the firm (See also (Doğan, 2013)). However, unlike Issa (2013) and Situm (2015) this study found that the impact is not statistically significant. Firms with low liquidity may search for ways to collect their receivables shortly and financing the organization in short term with bank and supplier credits.…”
Section: Liquidity As a Profitability Determinantcontrasting
confidence: 90%
See 1 more Smart Citation
“…The result shows that the profitability of the firms in manufacturing industry of Bangladesh is positively influenced by the Liquidity of the firm (See also (Doğan, 2013)). However, unlike Issa (2013) and Situm (2015) this study found that the impact is not statistically significant. Firms with low liquidity may search for ways to collect their receivables shortly and financing the organization in short term with bank and supplier credits.…”
Section: Liquidity As a Profitability Determinantcontrasting
confidence: 90%
“…In another study, Issa (2013) investigated some listed firms in agricultural sector of Nairobi (NSE) and found a statistically significant effect of liquidity that firms had on performance. Situm (2015) in a study, also found that increased liquidity reduces the probability of firm failure. Furthermore, identified that firm's liquidity in short term has significant and positive relationship whit the profitability.…”
Section: Firms Liquiditymentioning
confidence: 88%
“…In addition to measuring short-term risks, liquidity is also related with long-term firm performance and survival. Namely, many firm failure models confirmed that liquidity ratios were useful for failure prediction (Altman, 1968;Pervan, Pervan, & Vukoja, 2011;Situm, 2015). Such studies confirmed that increased liquidity reduces the probability of firm failure.…”
Section: Liquiditymentioning
confidence: 85%
“…Distress prediction models can be very useful in identifying distress from the early stages. Numerous attempts have been made to explain the phenomenon of financial distress, but no valid theory exists for bankruptcy prediction (Situm Mario, 2015). A theoretically sound, accurate, simple and widely used corporate failure prediction model for stakeholders is yet to be developed (Appiah et al, 2015).…”
mentioning
confidence: 99%